1972
DOI: 10.1002/cpt1972133317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activated charcoal on aspirin absorption in man Part I

Abstract: Part I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…A few studies have tried to answer this question either in experimental animals or in man. However, for obvious reasons the human studies have been made using relatively small doses of charcoal and drugs (Levy & Tsuchiya, 1972;Chin et al, 1973;Levy & Houston, 1976; The adsorption of PAS to activated charcoal was studied in vitro at pH 1.2 (0.1 M HCl) and pH 7.0 (0.05 M phosphate buffer) using charcoal-PAS ratios from 20:1 to 1:1. The incubations were performed at 37°C for 20 min as described earlier .…”
Section: Introduction Methodsmentioning
confidence: 99%
“…A few studies have tried to answer this question either in experimental animals or in man. However, for obvious reasons the human studies have been made using relatively small doses of charcoal and drugs (Levy & Tsuchiya, 1972;Chin et al, 1973;Levy & Houston, 1976; The adsorption of PAS to activated charcoal was studied in vitro at pH 1.2 (0.1 M HCl) and pH 7.0 (0.05 M phosphate buffer) using charcoal-PAS ratios from 20:1 to 1:1. The incubations were performed at 37°C for 20 min as described earlier .…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Different food components can have different effects, and food may interact in opposite ways, even with drugs that are chemically related (Melander, 1978). Therefore, the net effect of food and activated charcoal on In man it has been demonstrated that food reduces the inhibiting effect of charcoal on aspirin absorption: the percentage of a 1 g aspirin dose recovered in the urine, when 10 g activated charcoal was given immediately after the aspirin, was about 60% for fasted subjects and 75% for subjects who had eaten a standard -I I .E 2. breakfast 15 min prior to the test (Levy & Tsuchiya, 1972). In dogs, however, the opposite effect was observed when they had been fed 1 h before the test (Atkinson & Azarnoff, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it has been shown that scaling down procedures underestimate the adsorption of drug to charcoal for both aspirin and paracetamol (Levy & Houston, 1976;Levy & Tsuchiya, 1972). This has been attributed to non-specific competition of gastric contents for adsorption on charcoal, the relative effect of which diminishes as the absolute dose of charcoal increases even though the ratio of drug to charcoal is kept constant.…”
Section: Methodsmentioning
confidence: 99%